Reconstruction of soft tissue defects in the distal third of the leg, ankle, and foot: a meta-analysis (2015)
Management of soft tissue defects in the distal third of the leg, ankle and foot has evolved over time despite its challenges. No option of coverage is universally recommended for defects in this region of the body. Our objectives were to review and analyze outcomes of reported options of reconstruction of soft tissue defects in this region. We conducted a search of PUBMED and HINARI databases from 2000-2014 to identify reported options of reconstruction of soft tissue defects of the leg, ankle, and foot. Pooled data from suitable articles were analyzed and the success and complication rates as well as the relative risks for failure and complications were computed. One thousand and thirty two articles were retrieved out of which thirty three met the inclusion criteria for analysis. All the 33 articles were uncontrolled cohort and descriptive studies. There were 14 reports on sural artery flap, 6 on perforator-based flaps, and 5 on free flaps. Cross leg flaps, adipofascial, peroneus brevis, and hemisoleus muscle flaps were reported in two studies each while medial plantar, supramalleolar, and skin grafts were reported in one study each. Flap failure was the commonest complication with free flaps while reconstruction with skin grafts had the lowest failure rate. Free flaps were, however, versatile for reconstruction of complex defect. Conclusively, meticulous planning is required in the reconstruction of defects of the lower third of the distal third of the leg, ankle, and foot in order to use the most appropriate method for best outcomes.